Density Variant Carbon Nanotube Interconnected Solids. (3rd February 2015) - Ozden, Sehmus; Tiwary, Chandra Sekhar; Hart, Amelia H. C.; Chipara, Alin Cristian; Romero‐Aburto, Rebeca; Rodrigues, Marco‐Tulio F.; Taha‐Tijerina, Jaime; Vajtai, Robert; Ajayan, Pulickel M.
Abstract : The scalable fabrication of 3D macroscopic solids with controllable densities of nanoscale junctions between carbon nanotubes (CNTs) is reported using chemical vapor deposition. The nanoscale intermolecular junctions result in porous solids with high thermal stability, electrical conductivity, excellent mechanical properties, and structural stability in concentrated acids, bases, and organic solvents. Such CNT solids represent the next generation of carbon‐based materials with potential for a broad range of applications.